Imagining Adam’s Dream: Keats’s Chamber of Maiden Thought in The Eve of St. Agnes - Alexander Linker, Laura (Miscelánea: A Journal of English and American Studies, 2006)
The purpose of this essay is to explore how Keats constructs Porphyro’s and Madeline’s physical and metaphysical identities in the poem and to examine the relationship of gender to the artistic process, which Keats presents lyrically as a vision of the poetical character outlined in his letters. Based on Keats’s description of “Adam’s Dream”, the poetic process, the character of the poet, and the chamber of maiden thought in his letters, I argue that, in the poem, Porphyro represents the androgynous poet surrendering his masculine identity for a feminine one —Madeline’s. Though Madeline occupies a traditional Petrarchan role as muse to Porphyro, she nevertheless displays imaginative longings for divine inspiration— qualities typically associated with the poet, not his muse.